Development of Discovery Learning-based E-modules Using PDF Flip Professional Software Integrated with the Website as An Alternative to Learning Physics During the Covid 19 Pandemic - Wayan Sudarsana; Sarwanto Sarwanto; Ahmad Marzuki (Postgraduate, University of Mataram, 2021)
This research aims to determine whether the development of discovery learning–based e-module using the professional PDF flip software integrated with the website can be an alternative in learning physics during the COVID-19 pandemic. This type of research is a preliminary study with qualitative descriptive research methods. The instrument used is a questionnaire with four categories, which is then distributed to teachers and students. The subjects in the study were physics teachers and students at SMA Negeri 3 Palu and SMA Karunadipa Palu. The data analysis used a qualitative description of the answer given by teachers and students. The results of preliminary studies show that: COVID-19 pandemic resulted in a look place online so that teachers needed teaching materials and practical media to be used without face-to-face learning. The research concludes that e-module development-based discovery learning using professional PDF flip software is integrated with the website as an alternative in learning physics during the COVID-19 pandemic.